2015
DOI: 10.5539/gjhs.v8n1p133
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Imputation to Correct for Nonresponse Bias: Application in Non-communicable Disease Risk Factors Survey

Abstract: Background:This study was carried out to use multiple imputation (MI) in order to correct for the potential nonresponse bias in measurements related to variable fasting blood glucose (FBS) in non-communicable disease risk factors survey conducted in Iran in 2007.Methods:Five multiple imputation methods as bootstrap expectation maximization, multivariate normal regression, univariate linear regression, MI by chained equation, and predictive mean matching were applied to impute variable fasting blood sugar. To m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…So, our findings are consistent with the literature indicating that performance of MI methods depends on the target analysis and rate of missing data and can be improved by selection of proper variable transformation [6]. Besides, as some studies have also shown in other settings, there are some MI methods with almost similar performance that can considerably correct for nonresponse bias in STEPS surveys [4,18,21,22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…So, our findings are consistent with the literature indicating that performance of MI methods depends on the target analysis and rate of missing data and can be improved by selection of proper variable transformation [6]. Besides, as some studies have also shown in other settings, there are some MI methods with almost similar performance that can considerably correct for nonresponse bias in STEPS surveys [4,18,21,22].…”
Section: Discussionsupporting
confidence: 91%
“…In estimation process, survey setting and weights, as defined by Iran' STEPS survey team, were taken into account. There is enough material available for more detailed information on sampling, weighting, and survey setting of the Iran's STEPS survey [18].…”
Section: Simulationmentioning
confidence: 99%
“…We believe this approach can either complement or substitute for more complicated and time-consuming methods of weighting variables or constructing propensity models that require access to population characteristics from which the sample was drawn. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…■ We believe this approach can either complement or substitute for more complicated and time-consuming methods of weighting variables or constructing propensity models that require access to population characteristics from which the sample was drawn. 22,23 ■ To help uptake of successive wave analysis among public health researchers, journal editors and reviewers can ask that researchers provide evidence of assessing nonresponse when applicable to their study methods and context. Doing so will strengthen the evidence base produced by epidemiological studies in the field.…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…Multiple imputation techniques are often applied to fill the information gaps (Miri et al 2016). For binary exposure, several studies have combined imputation techniques with PS analysis (Doidge 2018;Eulenburg et al 2016;Hayes and Groner 2008;Hill 2004;Hsu and Yu 2019;Kupzyk and Beal 2017;Lavori et al 1995;Mitra and Reiter 2016;Qu and Lipkovich 2009;Rosenbaum and Rubin 1984).…”
Section: Introductionmentioning
confidence: 99%